Modulatory effect of pomegranate peel extract on key regulators of ovarian cellular processes in vitro - Kolesarova, Adriana; Baldovska, Simona; Kohut, Ladislav; Vasicek, Jaromir; Ivanisova, Eva; Arvay, Julius; Duracka, Michal; Roychoudhury, Shubhadeep (Frontiers in Endocrinology, 2023)
In this study, response of ovarian cells (human granulosa cell line HGL5, and human adenocarcinoma cell line OVCAR-3) to short-term pomegranate peel extract (PPE) treatment (for 24 hours in cell culture) was evaluated in vitro. Quantitative and qualitative screening of polyphenols revealed punicalagins α and β as major polyphenolic components. Total phenolic content (TPC) was 93.76 mg GAE/g d.w. with a high antioxidant activity of 95.30 mg TEAC/g d.w. In OVCAR-3, PPE treatment inhibited the metabolic activity, and increased cyclin-dependent kinase 1 (CDKN1A, p21) level at the highest dose, but not in HGL5. Flow cytometry analysis could not detect any significant difference between proportions of live, dead, and apoptotic cells in both cell lines. Reactive oxygen species (ROS) revealed an antioxidant effect on HGL5, and a prooxidant effect by stimulating ROS generation in OVCAR-3 cells at the higher doses of PPE. However, in contrast to HGL5, PPE treatment decreased release of growth factors – TGF-β2 and EGF at the highest dose, as well as their receptors TGFBR2 and EGFR in OVCAR-3 cells. PPE also influenced steroidogenesis in granulosa cells HGL5 by stimulating 17β-estradiol secretion at higher doses. In conclusion, the present study highlighted the bioactive compounds in pomegranate peels and the possible mechanisms of action of PPE, shedding light on its promising role in ovarian cancer (chemo)prevention and/or management.